Anti Cheat of Computer Based Test Application in Enterpreneurship Exams using The Multiplicative Random Number Generator Method - Badrul Anwar; Ganefri Ganefri; Asmar Yulastri; Dicky Nofriansyah; Asyahri Hadi Nasyuha (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
STMIK Triguna Dharma is one of the best private universities in North Sumatra in the field of ICT. To realize an entrepreneurial university, it is necessary to have maximum efforts from all elements of management and the foundation. This reflects the quality of learning and good higher education governance. So far, there have been many test implementation techniques in several schools, such as conventional and CBT concepts. Based on the observed phenomena, the CBT that was implemented had problems including fraud in the implementation. Referring to this problem, STMIK Triguna Dharma innovates by building a web-based anti-cheat CBT application by adopting the Multi Random Number Generator Method. The advantage of this method is that it is able to randomize questions and answers with the available question packages so that this effort can properly reduce cheating, for example on semester exams. The results of this study are a web-based anti-cheat application which adopts the MRNG method which is expected to be a solution and can be used by STMIK Triguna Dharma in conducting semester exams, especially in entrepreneurship courses.